Microbiota-based markers predictive of development of Clostridioides difficile infection - Berkell, Matilda; Mysara, Mohamed; Xavier, Basil Britto; van Werkhoven, Cornelis H.; Monsieurs, Pieter; Lammens, Christine; Ducher, Annie; Vehreschild, Maria J. G. T.; Goossens, Herman; de Gunzburg, Jean; Bonten, Marc J. M.; Malhotra-Kumar, Surbhi; et al. (Nature Communications, 2021)
Antibiotic-induced modulation of the intestinal microbiota can lead to Clostridioides difficile infection (CDI), which is associated with considerable morbidity, mortality, and healthcare-costs globally. Therefore, identification of markers predictive of CDI could substantially contribute to guiding therapy and decreasing the infection burden. Here, we analyze the intestinal microbiota of hospitalized patients at increased CDI risk in a prospective, 90-day cohort-study before and after antibiotic treatment and at diarrhea onset. We show that patients developing CDI already exhibit significantly lower diversity before antibiotic treatment and a distinct microbiota enriched in Enterococcus and depleted of Ruminococcus, Blautia, Prevotella and Bifidobacterium compared to non-CDI patients. We find that antibiotic treatment-induced dysbiosis is class-specific with beta-lactams further increasing enterococcal abundance. Our findings, validated in an independent prospective patient cohort developing CDI, can be exploited to enrich for high-risk patients in prospective clinical trials, and to develop predictive microbiota-based diagnostics for management of patients at risk for CDI.
The ANTICIPATE study group Annemarie Engbers, Ute Merle [und viele weitere Verfasser]
Gesehen am 09.06.2021